Investigation of the interaction of charge motion and residual gas concentration in an optically accessible SI engine - Mederer, Thomas; Wensing, Michael; Leipertz, Alfred (SAE Technical Papers, 2013)
In spark-ignition engines, high exhaust gas recirculation (EGR) rates have demonstrated their potential in reducing fuel consumption and emissions. However, irregular combustion at high residual gas concentrations limits the EGR rates. The following study presents a strategy that has been developed to investigate the influence of complex charge motion on mixture formation and combustion for high residual gas concentrations with the aim of extending these limits. An optically accessible single-cylinder SI Engine with direct injection was used to measure the charge distribution by means of laser induced fluorescence (LIF). A special device inside the inlet pipe gave the possibility to generate a defined swirl motion overlaying a tumble motion given by the design of the inlet ports. A developed uniformity index to evaluate the LIF results and an adjustable supply of premixed residual gas into the intake air system helped to study the effect of increasing EGR rates on charge distribution and combustion for different charge motions. The tracer acetone was injected into the intake air system to localize residual gas in the combustion chamber. Results obtained in typical part load operation show fastest mixing and most stable burning at high EGR rates for a charge motion combining a standard tumble flow with additional swirl. Copyright © 2013 SAE International.
Created from Fastlane, Scopus look-up